General Anesthesia in the First 36 Months of Life. - Schüttler, Christina; Münster, Tino; Gall, Christine; Trollmann, Regina; Schüttler, Jürgen (Deutsches Ärzteblatt international, 2021)
BACKGROUND: Experimental data have shown that the developing brain is especially vulnerable to exogenous noxious substances. The potential effects of anesthetic drugs on brain growth and development are a matter of concern. Clinical studies of children who underwent general anesthesia in their earliest years can make a major contribution to our understanding of the effects of anesthetic drugs on infants and toddlers (i.e., children under age 5). METHODS: Children born at term during the years 2007-2011 who were exposed to general anesthesia before their third birthday were included in the study. Data on general anesthesia were retrospectively evaluated, and the overall intelligence quotient (IQ) was determined prospectively as the primary target parameter. Children who had not been exposed to general anesthesia were recruited as a control group. The non-inferiority threshold was set at a difference of 5 IQ points out of a consideration of clinical relevance. RESULTS: 430 complete data sets were available from exposed children and 67 from members of the control group. The exposed group achieved a mean IQ score of 108.2, with a 95% confidence interval of [107; 109.4]; the corresponding values in the control group were 113 [110; 116.1]. Both groups achieved a mean score that was higher than the expected 100 points. After adjustment for age, socioeconomic status, and sex, the difference between the two groups was 2.9 points [0.2; 5.6], indicating a significantly better outcome in the control group than in the exposed group. The non-inferiority threshold of 5 IQ points was within the confidence interval; thus, non-inferiority was not demonstrated. CONCLUSION: The fact that both groups achieved a higher IQ score than the expected 100 points may be attributable, at least in part, to the restriction of the study to children born at term. The results indicate that general anesthesia in early childhood is not associated with markedly reduced intelligence in later years, although noninferiority could not be demonstrated.
EVALuna2:491351